Factors Causing Reform of Marriage Law in the Islamic World - Sinulingga, Ahmad Yasir; Ananda, Faisar; Irwansyah, Irwansyah (Faculty of Law, Universitas Pattimura, 2025)
Introduction: The reform of Islamic marriage law is fundamentally influenced by many factors.Purposes of the Research: This paper aims to find out what factors caused the reform of marriage law in the Islamic world, and what the wisdom of the reform of marriage law is for the Muslim community.Methods of the Research: This research employs the library study approach (library research). Primary sources of information are derived from publications pertaining to the discourse on the reform of marriage law in the Islamic world.Results of the Research: The results of the study show that there are many things that become factors causing the reform of the marriage law, but the main factor is the development of the times in terms of socio-cultural changes so that new problems arise that need new laws in response to this. While the wisdom of the renewal of the marriage law is to keep the teachings of Islam in the family field still accepted by modern society.